Вплив кремнієвмісних мінералів і сумішей на їх основі на алелопатичний режим прикореневого ґрунту під 30-річними насадженнями яблуні та персика - Didyk, N.P.; Ivanytska, B.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to study the effect of the application of siliceous minerals and organomineral mixtures on their basis to improve allelopathic regime of the rhizosphere soil under 30-year apple and peach trees in the model laboratory experiments. Material and methods. The object of the study is the rhizosphere soil collected from under the 30-year-old apple and peach trees of the collections of M.M. Gryshko National Botanical Garden of the NAS of Ukraine at the phase of bud formation. Siliceous minerals and mixtures based on them were applied at a concentration of 1 : 1000 and incubated in the soil for 5 months. Before the experiments started, the content of nutrients, humus and pH of soil solution had been determined. During the incubation period, the allelopathic activity of the soil was determined every two weeks by direct bioassay technique. The content of free phenolic compounds in the soil solution was analyzed after 14 and 104 days after the start of the experiment. Statistical analysis was conducted using the programs Statistica 10.0 and Microsoft Excel 7.0. Results. It was established that all investigated minerals and mixtures on their basis contributed to the reduction of phytotoxicity of the soil and the content of free phenolic compounds in the soil solution. The effect size positively correlated with the term of their incubation in the soil. The mixture of peat with tripoli in the ratio of 70 : 30 was the most effective in improving the allelopathic regime of soil from under the old apple and peach plantings. Conclusion. The prospects of application of siliceous minerals mixed with peat and sapropel to overcome allelopathic soil sickness in 30-year-old apple and peach plantings have been shown.